ANALISIS PETA MUTU PENDIDIKAN PADA JENJANG SEKOLAH MENENGAH KEJURUAN (SMK) DI PROVINSI ACEH. - Herliana Herliana (JURNAL SERAMBI ILMU, 2018)
This study aims to analize the result of quality mapping of vocational schools as a part of the educational quality assurance in Aceh province in 2017. The school mapping has been conducted nationally for the past two years since 2016 to 2017, which in Aceh has been involving all schools in 23 districts. The quality mapping is conducted using web based instruments for respondences teachers, head teacher, students and school committee. This analysis is a comparative description of the result based on the 8 national standards of education, using five categories to meet the highest level of the standards. The results of this research showed that the quality of vocational schools in Aceh is below the national standars; including the graduates, the content of curriculum, teaching and learning process, management, teachers and education personels, infrastructure andequipment, evaluation, and finance. The content of curriculum showed the highest score 5.04, comparing with nasional 4.87. It means that the quality of vocational school in Aceh is better that the average quality of vocational schools in Indonesia, despite this is remain below the expected national standard. Nevertheless, the lowest score is the standard of teachers and education personels; 3.33. Comparing to the average score of national 2.98, the quality of vocational school of Aceh in general is better, despite this is remain below the expected quality according to the national standard.